Deskripsi Literasi Pemahaman Mahasiswa melalui Model Pembelajaran Berbasis SDG 4 - Salma Samputri; Rifda Nur Hikmahwati Arif; Selviyanti Bassi; Evi Wahyuni (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2025)
This study aims to (1) describe the average score of students’ comprehension literacy related to Sustainable Development Goal 4 (SDG 4: Quality Education) and (2) describe the percentage of each indicator of students’ comprehension literacy through SDG 4-based learning. The research is a descriptive study with a quantitative approach. The population consists of students of the Science Education Department, cohort 2025. The sampling technique used was saturated sampling, in which the entire population was taken as the sample, totaling 101 students who were enrolled in an introductory education course. The instrument used was a non-test questionnaire on SDG 4 literacy consisting of 20 items. The questionnaire employed a Likert scale covering aspects of knowledge, understanding, attitude, concern, and intention to act. Data were analyzed using descriptive statistics by calculating the mean score and the percentage of responses based on five indicators of students’ comprehension literacy toward SDG 4-based learning. The results show that (1) the average score of students’ SDG 4 comprehension literacy is 69.76, which falls into the high category; and (2) the percentage for each indicator of students’ comprehension literacy through SDG 4-based learning is as follows: (a) Very Low and Low = 0%, (b) Moderate = 1%, (c) High = 83%, and (d) Very High = 16%.